Religion and politics: examining the impact of faith on political participation - Omelicheva, Mariya (Religion, state & society, 2018)
This study examines the relationship between religion and political activity. It theorises religious influences on political activity and tests the impact of various religious factors on political participation in a large cross-national sample (1981-2014). This study integrates longitudinal data from the aggregated World Values Survey with country-level data in the hierarchical multilevel analysis that allows teasing out the individual-level religious influences, including membership in religious organisations, religiosity and self-identification with various religious denominations, and the country-level impacts. The temporal and spatial coverage of the data used in the study includes more than 65% of the world's population. The seven types of political participation examined in the study include signing petitions, joining in boycotts, participating in demonstrations, taking part in unofficial strikes, occupying buildings and factories, voting and membership in political parties. We find that religion matters but not always in the expected ways. Religiosity, by itself, often serves as a deterrent rather than mobilising force for political engagement, regardless the denominational differences. It is the membership in religious organisations and other voluntary associations of a secular nature that make individuals more likely to engage in political activity.